(untitled) (Medical Forum Monthly, 2020)
Objective: To examine the effectiveness of dexamethasone and ondansetron combination and compare with ondansetron only for reducing the incidence of postoperative nausea and vomiting in patients undergoing laparoscopic cholecystectomy. Study Design: Randomized controlled trial Place and Duration of Study: This study was conducted at the Department of Surgery DHQ Teaching Hospital Mirpur AJK from December 2018 to December 2019. Materials and Methods: One hundred and forty patients of both genders with ages 20 to 65 years undergoing laparoscopic cholecystectomy were enrolled in this study. Patients were divided into two groups I and II. Each group comprised 70 patients. Group I received combine dose of ondansetron and dexamethasone while group II received ondansetron only. Efficacy between both groups was examined at 24 hours after surgery. Results: There were 50 (71.42%) patients were females and 20 (28.57%) were males in group I while in group II 48 (68.57%) were females and 22 (31.43%) were males. No significant difference was observed regarding mean age in both groups (p=>0.05). In group I 5 (7.14%) patients had nausea/vomiting while in group II 25 (35.71%) patients had nausea/vomiting. A significant difference was observed between both groups I and II regarding effectiveness of doses with p-value 0.001. Conclusion: Dexamethasone and ondansetron combination is very effective for preventing postoperative nausea and vomiting in patients with laparoscopic cholecystectomy.